An Attempt towards Debunking the Myth that Women‟s Labour is Inconsequential - Mukherjee, Gitasri (International Journal of Psychosocial Rehabilitation, 2020)
In a patriarchal society like ours, men are considered the breadwinners of the family and women, the homemakers. Therefore, any work that a woman does, is not valued much because it does not contribute directly to the income of the family. However, in this process their untiring efforts and the amount of time they spend in taking care of the household chores, such as preparing meals, getting kids ready for school, managing rations, cleaning, washing etc. remain unnoticed. It is believed to be her responsibility. The process of socialization is instrumental in making one learn the expected gender roles and accept the norms. It prepares a girl from the very beginning to find the true meaning of her life in making others happy. The present paper makes an attempt to bust the myth that women’s labour is inconsequential or minimal, critically examines the reasons and focuses on the possibilities of bringing a change in the mindset of people.